Mechanical properties of recycled aggregate concrete containing ternary blended cementitious materials - Shaikh, Faiz (Elsevier BV, 2017)
This paper presents the effect of silica fume (SF) on early-age and long-term mechanical properties of recycled aggregate concrete containing slag. In this study six series of mixes are considered. The first series is control concrete containing 100% ordinary Portland cement (OPC) and 100% natural aggregates. The second series is similar to the first series in every aspect except the natural coarse aggregate (NCA) which was partially replaced by 50% (by wt.) recycled coarse aggregate (RCA). The third series is also similar to the second series except the OPC which is partially replaced by 50% slag. The effects of 5, 10 and 15% (by wt.) SF on mechanical properties of concrete is evaluated in fourth, fifth and sixth series, respectively. Compressive strength, indirect tensile strength and modulus of elasticity of above concretes are measured at 3, 7, 28, 56 and 91 days. Results show that the addition of 50% slag significantly reduced the above mechanical properties of concrete containing 50% RCA at early age. Among three SF contents, the 10% SF improved the above mechanical properties of recycled aggregate concrete containing slag at early ages (3 and 7 days) as well as at 28 days. The addition of 10% SF also improved the 56 and 91 days compressive and tensile strengths of recycled aggregate concrete containing slag. It is also found that the long-term (56 and 91 days) compressive and tensile strengths of recycled aggregate concrete containing slag and 10% SF are even higher than the OPC concrete containing 50% RCA and control concrete, respectively. It is also observed that the slow pozzolanic reaction of slag contributed to the long-term compressive and tensile strengths of recycled aggregate concrete containing slag and 10% SF. Strong correlations of measured compressive strength with indirect tensile strength and elastic modulus of above environmentally friendly concretes are also established.